Being known - Gunn, Robin Jones, 1955- (Gunn, Robin Jones, 1955- Haven makers series, 2020)
"From the bestselling author of Becoming Us comes a novel unpacking loss, doubts, friendship, and the hard questions we ask of God and those we love. After her mom passed away, Jennalyn was in the midst of moving, having a baby, and helping her husband work toward his dream job. At the time, she thought she processed the shock and loss, but only now that Jennalyn has two small children, a lovely new home, a lucrative side hustle with her art, and a husband who is always working does she feel the full impact of the loss. Enter an old boyfriend who knew Jennalyn well and who shares many fond memories of her mom. Jennalyn begins to doubt her marriage and all her other life choices ever since her mom passed away. It takes the power of truth, close friends who know her well, and a series of choices at the heart level before Jennalyn can surface from the confusion and see with clarity where her life is headed."--